Chile : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that over the past two decades, Chile has adhered to a sound and consistent policy framework. During 2000-03, the actual overall balance of the central government registered a deficit of just below 1 percent of GDP. Since the beginning of 2004, economic activity has picked up, in the context of a favorable external environment. The global economic recovery has helped boost export demand, particularly copper, the price of which has nearly doubled since end-2002.